Transorbital ultrasound measurement of the optic nerve sheath diameter (ONSD) as a screening tool for raised intracranial pressure in an acute care setting in children - Padayachy, Vaishali (Department of Surgery, 2016)
Background: Acute care management of pediatric traumatic brain injury (TBI) can be challenging. Early and reliable diagnosis of intracranial pressure (ICP) in children following TBI is vital in optimizing outcome. Clinical findings of raised ICP can be non-specific and are often missed in minor injuries, leading to severe consequences. The use of a simple, quick, accurate, non-invasive technique to assess ICP can be invaluable in this setting. Based on the hypothesis that acutely raised ICP will result in an enlargement of the optic nerve sheath diameter (ONSD), this study aimed to demonstrate the efficacy of transorbital measurement of the ONSD as a routine screening tool in pediatric TBI. Methodology: This was a prospective observational analysis of a pediatric cohort of patients with head injury, treated in the trauma unit. All children included in the study were clinically assessed, and had indications for cranial computer tomography (CT) scan. All optic nerve sheath imaging was conducted by a single investigator, experienced in the use of ultrasound for emergency care. ONSD measurements were conducted using a high frequency, linear array probe. Patients were sedated and ONSD measurement was performed prior to or immediately after CT imaging. A total of 12 images were obtained in each patient, 3 axial and 3 sagittal images in each eye and the mean ONSD was calculated. ONSD measurements were analyzed in relation to clinical severity, CT findings of raised ICP and outcome of the patient.